Accuracy of Transforming Growth Factor-Beta in Serum and Synovial Fluid as Rheumatoid Arthritis Prognostic Factors - Almousawy, Ali J.; Darweesh, Mayyada F. (South Eastern European Journal of Public Health, 2024)
Background: Rheumatoid arthritis (RA) An autoimmunity of the joints which is now seen as a major public health concern. Therefore, finding new biomarkers is crucial to improve RA sufferers' quality of life. Several cytokines increased the inflammatory cascade which linked to pathophysiology of RA. This investigation aimed to determine the validity of transforming growth factor-beta-1 (TGF-β1) in synovial fluid and serum as prognostic factor and which one is better for rheumatoid arthritis disease follow up. Material and Methods: In Al-Saddar Medical City Rheumatology Unit in the Najaf governorate, 80 patients were included in case-control research. These patients were identified by specialized who classified the patients according to stages of disease into mild stage (stage 1 and 2) and aggressive (stage 3 and 4 who had knee effusion and synovial fluid separation). Venous blood samples (3ml) drawn from patients and controls were transferred to a gel tube for serum separation that used to measure the TGF-β1 level in accordance (BT LAB/China), RF level and anti-CCP level by ELISA assay. knee synovial fluid was collected from RA patients in aggressive stage and from patient suffering from knee trauma as control group which included 18 patients not have RA. The result demonstrated that Females and aged individuals in AL-NAJAF province more incidence with RA disease. TGF-β1 serum level increased significantly with disease severity and positive correlated with ACCP autoantibody, according to ROC prognosis analysis AUC of TGF-β1 serum level was excellent 0.9 with 100% sensitivity and specificity. While ROC analysis for TGF-β1 synovial fluid was 0.8 with 77.8% sensitivity and 86.7% specificity Conclusion: Using ROC analysis, which supported good TGF level in both serum and synovial fluid diagnosis accuracy and enabled more sensitive and precise discrimination in RA disease. Instead of using synovial fluid separation as a diagnostic for excellent prognosis in RA disease, TGF-β1 and ACCP blood levels can help patients avoid discomfort and stress.